2015
DOI: 10.1063/1.4923356
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity study of multi-layer active magnetic regenerators using first order magnetocaloric material La(Fe,Mn,Si)13Hy

Abstract: We present simulation results of multi-layer active magnetic regenerators using the solid-state refrigerant La(Fe,Mn,Si) 13 H y. This material presents a large, however quite sharp, isothermal entropy change that requires a careful choice of number of layers and working temperature for multi-layer regenerators. The impact of the number of layers and the sensitivity to the working temperature as well as the temperature span are quantified using a one dimensional numerical model. A study of the sensitivity of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…To study the AMRs using different geometries, a 1D transient numerical model developed at the Technical University of Denmark [46,47] is used. The energy equations for the heat transfer liquid and solid refrigerant [25] can be expressed as:…”
mentioning
confidence: 99%
“…To study the AMRs using different geometries, a 1D transient numerical model developed at the Technical University of Denmark [46,47] is used. The energy equations for the heat transfer liquid and solid refrigerant [25] can be expressed as:…”
mentioning
confidence: 99%
“…This addresses one of the major bottlenecks to the uptake of the technology: the need to reduce expensive rare‐earth element based permanent magnets. (iii) Resolving issues of working temperature in magnetic refrigerators: literature has shown that the cooling power of a magnetic regenerator may decrease by about 90% if T C of the material is just a few kelvins from the absolute working temperature , which can vary significantly during 1 day. Therefore, controlling T C is of extreme relevance for application and the application of pressure to fine tune performance maxima would lead to an extension of the working fridge temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…It is of great importance to examine materials with a large MCE that may work at different temperature ranges, especially for around room temperature [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Early studies indicated that high-purity Gd shows considerable MCE near room temperature, with nice mechanical properties [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising room temperature magnetic refrigerants is La(Fe x Si 1−x ) 13 hydride [11]. However, the inherent brittleness and hydrogen cracking of the 1:13 phase during the hydrogenation break the hydrides into powder, which is not in conformity with the requirements of shape for use in magnetocaloric regenerators [9,10,16]. Lyubina et al obtained porous La(Fe,Si) 13 materials by hot pressed (HP) La-Fe-Si particles which exhibited better mechanical properties and lower hysteresis compared with bulk materials [10].…”
Section: Introductionmentioning
confidence: 99%